THEMATIC DEVELOPMENT ON STUDENTS’ ANALYTICAL EXPOSITION TEXTS A CASE OF THE FOURTH SEMESTER STUDENTS IN THE ACADEMIC YEAR 2014/2015 - Setiawati, Novita; Hapsari, Intan Permata; Priyatmojo, Arif Suryo (ELT Forum: Journal of English Language Teaching, 2017)
This final project is based on a study endeavored to examine the development of analytical exposition texts written by the fourth semester students of Universitas Negeri Semarang in the academic year of 2014/2015 who took Genre-based Writing class . The objective of the study is to examine to what extent the students develop their analytical exposition texts, in terms of Thematic Development. This study is a written discourse analysis in which the data collected are in the form of written texts. To examine Thematic Development, Thematic Structure must be found first. The data were divided into clauses and analyzed to discover their Thematic Structure using theory suggested by Gerot and Wignell (1995). Then the Themes and Rhemes were examined using Thematic Development theory suggested by Eggins (2004). Results show that unmarked Topical Theme and reiteration pattern are dominant on students’ texts because they are the simplest and easiest form of Thematic Structure and Thematic Development. In addition, some problems related to Thematic Structure and Thematic Development were found. In Thematic Structure analysis, one problem of empty Theme and three problems of empty Rheme were discovered, while more than half of total clauses did not have Thematic Development. These might indicate two points; first, the students of Genre-based Writing class are still novice writers. Second, they might not know about Thematic Development theory and how to employ it to develop their analytical exposition texts.